The evolution of barriers and facilitators to using a COPD app among older adults: results from a pilot study - Jeff Brady; Rachel F. McCloud; Erin Higgins; Aishwarya Mahesh; Keith LeJeune; Jon Black; Anil Singh (Frontiers in Digital Health)
PurposeAlthough older adults are more frequently adopting smartphone technologies, factors influencing decisions for uptake and continued use remain complex. This study explored how perceptions and use of a smartphone app changed from pre-adoption through initial use.MethodsParticipants were interviewed before, during, and after being introduced to a COPD app to assess their experiences with and perceptions of the app over a 4-month period.ResultsPrior to app introduction, participants reported technology, health behavior, and contextual barriers to engaging with health technology. After app introduction, many technology-based barriers lessened over time as participants became more familiar with the app. Other barriers, such as perceived lack of relevance and competing health and life concerns, remained as challenges to use.DiscussionResults point to the need for apps that can cater to the diverse needs and other life challenges of older adults. Opportunities for assistance from technical support lines, family, friends, and/or community are required.